Classification of Dissecting Aortic Aneurysm as a Guide for Surgical Management - L. Kulyk; D. Beshley; I. Protsyk; S. Lishchenko; V. Pezentiy; V. Averchuk; N. Hrabovskyy (Ukrainian Journal of Cardiovascular Surgery, 2020)
Mortality in acute dissecting type A aortic aneurysm remains high. The existing classifications are intended to give an accurate, and, very importantly (given the acute course of the pathology), a prompt answer to the clinician’s and the cardiac surgeon’s questions: how the patients should be treated, and which of them should undergo surgical intervention, and which procedure is to be used.Aim. A review and analysis of the existing classifications of dissecting aortic aneurysms and their transformation taking into account the advances in diagnostic technologies and methods of surgical management. The first classification was proposed by DeBakey; it systematized morphological variants of the disease and explained the origin of its accompanying phenomena such as heart tamponade, acute aortic valve insufficiency, and visceral and limb ischemia, but provided no guidelines on treatment techniques. A more recent Stanford classification was based on the principle of differentiation into conservative or operative approach. Owing to the use of CT and MRI angiography, new dissection subtypes were discovered and formulated in the Svensson classification. The Penn classification recommends that the choice of management can be based on the extent of aortic dissection, the site of the primary intimal tear, and the presence of malperfusion. The latest TEM classification identifies type A and type B dissection, as well as additional non-A-non-B type, in which the descending aorta and the arch, but not the ascending aorta, are involved. The most appropriate surgical procedures for the retrograde type A aortic dissection treatment are discussed as well.Conclusions. 1. The purpose of clinical classification of acute aortic dissection is, in addition to systematizing concepts and categories, facilitating the selection of an optimal state-of-the-art treatment method. 2. Introducing such classifications as Penn or TEM will bring to a common denominator the results of surgical management of acute type A dissection by unifying the characteristics of the patients and eliminating their deliberate or accidental pre-selection, which possibly accounts for the difference in mortality rates among different surgical groups.